Analysis on the influence of protection electrodes on the capacitance control rod position sensor. (November 2022) - Li, Yanlin; Qin, Benke; Bo, Hanliang
Abstract: Control rod position sensors are the core measuring components of the control rod drive system. For the capacitance control rod position sensor with protection electrodes, the sensitivity of the sensor is obtained by experiments. The calculated model of the sensor is established, and it is verified by experimental results. Based on the calculated model, the regulation method of protection electrodes on the unevenness of the sensitivity field of the sensor is systematically studied. Performance analysis of the sensitivity field, the structure design, and error analysis of the sensor are carried out. The results show that the sensor sensitivity is 0.007 563 pF/mm and the maximum measuring error can be limited within ±0.5 mm, which can meet the actual use demands. The results provide a new technical scheme for the subsequent research of capacitance control rod position sensors.